2020
DOI: 10.1002/jhbp.769
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of gadoxetic acid enhanced magnetic resonance imaging for posthepatectomy liver failure after a major hepatectomy

Abstract: Purpose: We assessed the usefulness of gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid enhanced magnetic resonance imaging for the prediction of posthepatectomy liver failure (PHLF) after a major hepatectomy. Methods:We reviewed 140 cases involving a hepatectomy of two or more sections between 2010 and 2016 (study cohort). We used the standardized remnant hepatocellular uptake index (SrHUI) which was calculated by: SrHUI = future remnant liver volume × [(signal intensity of remnant liver on hepatob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Briefly, in the study participation domain, three studies were marked as high risk as they had a limited number of participants (< 50 cases) coming from a single center and also did not state whether the patients were enrolled consecutively or not [ 20 , 22 , 33 ]. In the domain of prognostic factor measurement, three studies were labeled as high risk of bias as they did not demonstrate the interval between MRI exam and hepatectomy, the number of reviewers, and whether blinded to the clinical outcome or not [ 26 , 29 , 31 ]. Regarding the outcome measurement domain, one study showed moderate risk as it applied a less-common criterion for PHLF in which a subjective index, encephalopathy, was included [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, in the study participation domain, three studies were marked as high risk as they had a limited number of participants (< 50 cases) coming from a single center and also did not state whether the patients were enrolled consecutively or not [ 20 , 22 , 33 ]. In the domain of prognostic factor measurement, three studies were labeled as high risk of bias as they did not demonstrate the interval between MRI exam and hepatectomy, the number of reviewers, and whether blinded to the clinical outcome or not [ 26 , 29 , 31 ]. Regarding the outcome measurement domain, one study showed moderate risk as it applied a less-common criterion for PHLF in which a subjective index, encephalopathy, was included [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity and specificity were calculated in eleven studies (11/15), varying from 75 to 100% and from 54 to 93%, respectively. Eleven studies (11/15) supplied optimal cutoff values, among which one study verified it using a separate validation cohort with an accuracy of 0.80 [ 29 ]; another study yielded a sensitivity of 89% and a specificity of 92% in the validation cohort [ 31 ]. Detailed information about predictive accuracy of PHLF evaluated by gadoxetic acid–enhanced MRI parameters is listed in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some patients with an rHUI value greater than 0.410 had PHLF grade A, the incidence of PHLF of all grades was almost inversely proportional to the rHUI value ( r = –0.743, P = 0.013). Several studies 23 , 29 , 30 have reported that the parameters determined from EOB-MRI could predict PHLF in patients who underwent hepatectomy more accurately after adjusting for bodyweight (BW, kg) or body surface area (BSA, m 2 ). However, neither BW nor BSA improved the accuracy of rHUI for predicting grade B or C PHLF in the present cohort (AUC for rHUI adjusted for BW 0.595, for rHUI adjusted for BSA 0.622) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tsuruga et al reported that both the volume and function after PVE need to be measured to determine the optimal timing and surgical method of hepatic resection because of the functional transition lagging behind the increase in FLR (19) . 99m Tc-GSA combined with CT volumetry or gadoxetic acid-enhanced magnetic resonance imaging is useful for predicting the FLR (19) , (22) . Although the postoperative outcome after hepatic resection has been improved through various means, the rate of postoperative mortality or morbidity remains high.…”
Section: _ocurrence and Prevention Of Postoperative Complications After Hepatic Resection In Japanmentioning
confidence: 99%